2015
DOI: 10.1002/eji.201545480
|View full text |Cite
|
Sign up to set email alerts
|

TIGIT expression levels on human NK cells correlate with functional heterogeneity among healthy individuals

Abstract: Human NK cells display extensive phenotypic and functional heterogeneity among healthy individuals, but the mechanism responsible for this variation is still largely unknown. Here, we show that a novel immune receptor, T-cell immunoglobulin and ITIM domain (TIGIT), is expressed preferentially on human NK cells but shows wide variation in its expression levels among healthy individuals. We found that the TIGIT expression level is related to the phenotypic and functional heterogeneity of NK cells, and that NK ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
114
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 43 publications
8
114
1
Order By: Relevance
“…We found that TIGIT expression was significantly lower in adaptive NK cells compared with conventional NK cells. In a recent study, Wang et al have shown that different expression levels of TIGIT in NK cells from healthy individuals was associated with functional heterogeneity, and high TIGIT expression inversely correlated with IFN-γ production in response to IL-12 stimulation (20). Our results are in agreement with this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that TIGIT expression was significantly lower in adaptive NK cells compared with conventional NK cells. In a recent study, Wang et al have shown that different expression levels of TIGIT in NK cells from healthy individuals was associated with functional heterogeneity, and high TIGIT expression inversely correlated with IFN-γ production in response to IL-12 stimulation (20). Our results are in agreement with this study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TIGIT was found to be highly expressed on tumor-infiltrating lymphocytes (TILs), and co-blockade of TIGIT and PD-1 synergistically augmented CD8 + T cell activity against autologous tumor cells (19). TIGIT is also expressed on polyclonal NK cells (20), but little is known with respect to how TIGIT regulates human NK cell function in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…TIGIT is a novel key inhibitory checkpoint protein expressed on both NK and T cells with wide variation in its expression among individuals. [16, 17] Non-responding patients had elevated expression of TIGIT on T cells, which was even further upregulated in T cells and NK cells in patients with higher levels of IL-15. These data are consistent with recent in vitro reports that the blockade of the TIGIT pathway can increase NK cell IFNγ secretion and abrogate MDSC-mediated inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 TIGIT is an immune cell-specific immunoglobulin superfamily receptor of the CD28 family, which is present on the cell surface of 20%-90% of human NK cells with a median of 64%. 31 Similar to DNAM-1, TIGIT binds to CD112 and CD155; however, TIGIT affinity for CD112 and CD155 is higher compared with DNAM-1. 32 Moreover, TI-GIT is often coexpressed with DNAM-1 on NK cells, 31 making it likely that inhibition of NK cell function will dominate over activation when the NK cells encounter a target cell expressing CD155.…”
Section: Fig 2 Nk Cells Lyse Autologous Hiv-infected T Cells When Dmentioning
confidence: 93%
“…31 Similar to DNAM-1, TIGIT binds to CD112 and CD155; however, TIGIT affinity for CD112 and CD155 is higher compared with DNAM-1. 32 Moreover, TI-GIT is often coexpressed with DNAM-1 on NK cells, 31 making it likely that inhibition of NK cell function will dominate over activation when the NK cells encounter a target cell expressing CD155.…”
Section: Fig 2 Nk Cells Lyse Autologous Hiv-infected T Cells When Dmentioning
confidence: 93%